PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI KELAS V SD NEGERI 20 KURAO PAGANG KOTA PADANG - Syahanz Nazira; Atri Waldi; Muhammadi; Yesi Anita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was based on a field finding that students' learning achievement had not been optimal. The lack of implementation of problem-based learning (PBL) was one of the contributing factors. The purpose of this study was to describe how the problem-based learning (PBL) model could be used to improve students' learning outcomes in Pancasila education for fifth-grade students at SDN 20 Kurao Pagang, Padang City. This research employed Classroom Action Research (CAR) which combined both qualitative and quantitative approaches. The research was conducted in stages in two cycles consisting of planning, implementation, observation, and reflection. This study was carried out in the odd semester involving all fifth-grade students of SDN 20 Kurao Pagang, Padang City, totaling 26 students, and the classroom teacher as research subjects. The research findings indicate that the implementation of problem-based learning (PBL) has successfully improved students' learning outcomes in Pancasila education. This is evident from: (1) The teaching module initially achieved an average of 89.55% (B) in Cycle I, and then increased to 100% (AB) in Cycle II. (2) Teacher activity in implementing learning achieved an average of 91% (AB) in Cycle I and increased to 96.4% (AB) in Cycle II. (3) Student activity during learning achieved an average of 91% (AB) in Cycle I and increased to 96.4% (AB) in Cycle II. (4) Students' learning outcomes in Cycle I obtained an average of 81.6 (B), increasing to 93.3 (AB) in Cycle II.